2023
DOI: 10.1088/1748-0221/18/10/p10021
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning the digital mass-filter/ion-trap module for the MS SPIDOC prototype

Florian Simke,
Paul Fischer,
Tomislav Damjanović
et al.

Abstract: The combination of a linear quadrupole ion-filter and linear Paul trap operated with a rectangular guiding field for the filtering and accumulation of ions within the Mass  Spectrometry for Single Particle Imaging of Dipole  Oriented protein Complexes (MS SPIDOC) prototype [T. Kierspel et al.,  Anal. Bioanal. Chem., published online] is characterized. Using cationic caesium-iodide clusters, the ion-separation performance, ion accumulation, cooling, and ejection via in-trap pin electrodes is evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This discrepancy occurs because the theoretical resolution is calculated without considering ion conditions and confirms that the resolution calculated from q /Δ q only provides a conservative estimate . In similar results, Simke et al observed a large deviation between calculated and measured resolutions with an increased duty cycle …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy occurs because the theoretical resolution is calculated without considering ion conditions and confirms that the resolution calculated from q /Δ q only provides a conservative estimate . In similar results, Simke et al observed a large deviation between calculated and measured resolutions with an increased duty cycle …”
Section: Resultsmentioning
confidence: 99%
“…Though unique characteristics of digital QMF are theoretically predicted and have been preliminarily explored, ,,, application of digital waveform QMF technology for ICP-MS has not yet been reported. In this work, we experimentally investigate a proof-of-principle digital quadrupole mass filter coupled to an ICP source for elemental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For the digital quadrupole, the duty cycle can be changed which yields changes in the stability diagram from which a mass filter or ion trap can be constructed. For a square wave (50.0/50.0 duty cycle), the stability diagram is very similar to a sinusoidal quadrupole mass filter with a low mass cut off at q = 0.712 versus q = 0.908.…”
Section: Introductionmentioning
confidence: 99%
“…While the resolving field in the digital mass filter is generated by the duty cycle and not a DC field, the principles of the delayed DC ramp can still be applied. A square waveform applied to the prefilter allows the ion to traverse the a = 0 axis within the stable region prior to entering the main rod section with a rectangular waveform which yields ion selection. ,, This method requires four independent waveform outputs between the pre and postfilters and main rod sections. Alternatively, the rectangular waveforms can be directly applied to the main rod section and then capacitively coupled to the pre and postfilters, , requiring only two independent waveform outputs.…”
Section: Introductionmentioning
confidence: 99%